The Biological effects of uritica dioica extraction on some pathogenic Bacteria - Mohamed, Nadira Salman; khudair, Abdulaziz; Abdul-sattar, Hafsa; Ahmed, Dhuha; Esia, Mustafa; Alwahab, Laith Abd (Journal of Pharmacology and Drug Development, 2024)
The Urtica dioica is a flowering plant with long history of use in folk medicine and as a food source. Nettles grow all over the world in mild to temperate climates. The study aimed to determine the antibacterial activity of alcoholic watery extracts of dry leaves of Urtica dioica on some pathogenic microorganisms (E.coli, Staphylococcus. aureus). The Plants were collected in the early time of January from Baghdad. Deride leaves of Uritica were extracted using co-solvent (Water and ethanol) extraction way by Soxhelt apparatus for crude extraction, and use rotary evaporator to obtain power extract. The series dilution was prepared 50%, 25, 12.5w/v that use on Mueller-Hinton agar plates against the St.aureus, E.coli by using well diffusion method then compared with antimicrobial activity of many antibiotics against the same isolates using Kirby-Bauer method. The crude extract of U. dioica showed significant antibacterial effect against some clinically important pathogenic bacteria Staph.aureus : at the concentration 50% the inhibition zone was 20 mm , followed by 25% (14mm) , and12.5%(10mm), and E.coli : at the concentration 50% the inhibition zone was18mm , followed by 25%(12mm) ,and 12.5(8mm) respectively. Based on the obtained results it can be concluded that U. dioica is useful as antibacterial agent in treating infectious diseases.